"Secondary registrants": A new conceptualization of the spread of community control. (July 2023) - Leon, Chrysanthi S; Kilmer, Ashley R
U.S. policies influence worldwide responses to sexual offending and community control. Individuals in the U.S. convicted of sex offenses experience surveillance and control beyond their sentences, including public registries and residency restrictions. While the targets are the convicted individuals, many registrants have romantic partners, children, and other family members also navigating these restrictions. Findings from a qualitative study using written and interview responses from a hard-to-reach group—family members of registrants (n = 58)—reveal legal and extra-legal surveillance and control beyond the intended target. We argue that family members are "secondary registrants" enduring both the reach of sex offense policies into their personal lives and targeted harms because of their relationship with a convicted individual, including vigilantism and a "sex offender surcharge." Family members engage in advocacy work to ameliorate sex offense restrictions to counteract their own stigmatization and social exclusion. Conceptually, secondary registration captures the unique and expansive reach of policy, state surveillance, and coercion on registrant family members and raises new concerns about spillover harm. Secondary registration demonstrates an understudied example of the neoliberal penal practice of de-centering the state but with the addition of deep stigmatization and the spread of sovereign and vigilante violence onto families.